The Role of Self-Regulation Psychoeducation in Increasing Student Learning Motivation at Madrasah Tsanawiyah - Qotrun Nada Fitri; Eko Hardi Ansyah (Psikostudia : Jurnal Psikologi, 2024)
This study aims to see the significance of Self-Regulation Psychoeducation in improving learning motivation in students at MTS Hasyim Asy'ari Gempol, Researchers found a phenomenon that occurred in MTS in the less conducive learning environment during learning, to explore the cause of the problem researchers conducted interviews with 3 students and 3 teachers, from the results of the interviews researchers found problems with learning motivation in students, This study uses a quantitative experimental method with data collection techniques through pretest and posttest questionnaires compiled from a learning motivation scale, respondents in this study were 34 respondents who were selected using purposive sampling techniques based on predetermined criteria. The data analysis technique used the Paired T Test technique which was analyzed using JASP with the results stating that students received self-regulation psychoeducation material well as indicated by an increase with a large change in their learning motivation, it is concluded that Self-Regulation Psychoeducation has an influence in improving learning motivation of students at MTS Hasyim Asy'ari Gempol.Penelitian ini bertujuan untuk melihat signifikasi Psikoedukasi Regulasi Diri dalam meningkatkan motivasi belajar pada siswa di MTS Hasyim Asy’ari Gempol, Peneliti mendapati fenomena yang terjadi pada MTS pada kurang kondusifnya lingkungan pembelajaran pada saat pembelajaran berlangsung, untuk mendalami penyebab permasalahan peneliti melakukan wawancara kepada 3 orang siswa dan 3 orang Bapak dan Ibu Dewan Guru, dari hasil wawancara  peneliti menemukan terjadinya masalah pada motivasi belajar pada siswa. Penelitian ini menggunakan metode kuantitatif eksperimen dengan teknik pengambilan data melalui kuesioner pretest dan posttest yang disusun dari skala motivasi belajar, responden pada penelitian ini sejumlah 34 responden yang dipilih menggunakan teknik purposive sampling berdasarkan kriteria yang sudah ditentukan. Teknik analisis data menggunakan teknik Uji T yang dianalisis menggunakan JASP dengan hasil yang menyatakan bahwa siswa menerima dengan baik materi psikoedukasi regulasi diri dengan ditunjukkan adanya peningkatan dengan perubahan yang besar pada motivasi belajarnya, hal ini disimpulkan bahwa Psikoedukasi Regulasi diri memberikan pengaruh dalam meningkatkan motivasi belajar siswa MTS Hasyim Asy’ari Gempol.